2017
DOI: 10.1016/j.ejso.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

European temporal trends in the use of lymph node dissection in patients with renal cancer

Abstract: A trend towards lower LND was observed over time for RCC patients who underwent RN or NSS. LND is more frequently performed in younger patients, locally advanced diseases and in case of open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…This may be due to the surgeon's technical concerns about laparoscopically excising nodal tissue adjacent to the major vessels. Furthermore, retroperitoneal lymphadenopathy usually indicates a high probability of intraoperative adhesion and difficulty in separating the renal pedicle, which is not conducive to a laparoscopic operation (19).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the surgeon's technical concerns about laparoscopically excising nodal tissue adjacent to the major vessels. Furthermore, retroperitoneal lymphadenopathy usually indicates a high probability of intraoperative adhesion and difficulty in separating the renal pedicle, which is not conducive to a laparoscopic operation (19).…”
Section: Discussionmentioning
confidence: 99%
“…In the high-risk group, the survival bene t of LND were on the debate. Some retrospective analyses suggested that patients with high risk factors may bene t from LND [2][3][4][5][6] . Blute et al 2 and Crispen et al 5 found that patients with large tumor size (> 10 cm), high furhman grade, pT3-pT4, coagulative necrosis and sarcomatoid differentiation may bene t from LND.…”
Section: Discussionmentioning
confidence: 99%
“…Blute et al 2 and Crispen et al 5 found that patients with large tumor size (> 10 cm), high furhman grade, pT3-pT4, coagulative necrosis and sarcomatoid differentiation may bene t from LND. Capitanio et al 3,4,6 showed LND in the high-risk population like bulky tumor (> 10 cm), locally advanced or metastatic RCC could improve CSS. However, Feuerstein et al 12 and Gershman et al 13 observed that LND did not improve either CSM or OS across all stages, as well as in patients with increased risk of LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from EORTC showed 4% positive lymph nodes in cN0M0 patients, though with no survival benefit for extended LND (eLND). LND was therefore considered a staging procedure for lymph node metastases [194], influencing the current trend towards less use of LND [195].…”
Section: Lymphadenectomy 165mentioning
confidence: 99%